Damaged - Callow, Pamela (Don Mills, Ont. : MIRA, 2010)
When it appears that attorney Kate Lange's legal advice may have led to the brutal murder of the grandchild of one of her clients, Kate investigates in order to clear herself, and uncovers a conspiracy involving tissue brokering.
Keywords: Women lawyers -- Fiction; Donation of organs, tissues, etc. -- Fiction; Detective and mystery stories; Suspense fiction